The effectiveness of new teaching style on the students’ performance in vector calculus during movement control order - Firdaus Mohamad Hamzah; Nur Arzilah Ismail; Muhamad Alias Md Jedi; Noorhelyna Razali; Mohd Haniff Osman; Haliza Othman; Noraishikin Zulkarnain; Zambri Harun (Penerbit Universiti Kebangsaan Malaysia, 2022)
Teaching style becomes more challenging especially during Movement Control Order (MCO) due to Covid-19 pandemic. Thus, online learning be one of the new teaching styles used during MCO at all educations level. Therefore, to study the effectiveness of this style, this paper is to investigate the effect of the new teaching style on engineering student’s performance by determining the difference of overall scores between batches for each program in Vector Calculus (VC) course with ordinary and new teaching styles at Faculty of Engineering and Built Environment (FKAB), Universiti Kebangsaan Malaysia (UKM). Nonparametric test is used in this study is Mann Whitney to analyze the difference of the teaching style. The finding revealed that that students’ achievements in VC course could significantly distinguished by two batches of students with different teaching and assessment modes. In contrast, JKKP program shows there is no significant difference in overall scores between batches with different teaching styles.